2008
DOI: 10.1111/j.1755-3768.2007.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐application of single‐use eyedrop containers in an elderly population: comparisons with standard eyedrop bottle and with younger patients

Abstract: . Purpose:  To test whether patients aged ≥80 years can safely and successfully apply eyedrops from a single‐use eyedrop container without support, and to compare the results with those of younger patients using single‐use containers and older patients using standard eyedrop bottles. Methods:  Patients aged ≥80 years who had no physical or mental conditions hindering self‐application of eyedrops and actually did so because of glaucoma or dry eyes were included consecutively in the study group (n = 44) in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
2
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 21 publications
(40 reference statements)
1
81
2
9
Order By: Relevance
“…In other studies, the incidence of missing the eye when attempting to instil an eye drop has ranged from 6.8 to almost 20%, and the incidence of contaminating the bottle tip has ranged from 20 to over 70%. 14,21 Factors associated with poor technique have also been examined with older age, 15 limited school education, 15,16 and poor vision 16 reported to be of importance. Brown et al 13 found that patients attending private practice were more likely to have a good eye drop instillation technique and suggested that this was because the private patients received better instructions on the use of drops; however, the effect of education on instillation technique was not directly examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the incidence of missing the eye when attempting to instil an eye drop has ranged from 6.8 to almost 20%, and the incidence of contaminating the bottle tip has ranged from 20 to over 70%. 14,21 Factors associated with poor technique have also been examined with older age, 15 limited school education, 15,16 and poor vision 16 reported to be of importance. Brown et al 13 found that patients attending private practice were more likely to have a good eye drop instillation technique and suggested that this was because the private patients received better instructions on the use of drops; however, the effect of education on instillation technique was not directly examined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a poor technique is more likely in those with poor manual dexterity, poor vision, limited schooling, and older age. 1,15,16 There is, however, little evidence as to whether education regarding how to self-administer eye drops is associated with a better eye drop instillation technique. Lack of education is likely to be a large problem, as when clinicians prescribe eye drops, proper explanation and demonstration of how the eye drops should be used is often neglected.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Dietlein et al, 15 it was reported that glaucoma or dry eye patients, aged 80 years or older, experienced more difficulty in opening and applying drops from single-dose containers compared with conventional eye drop bottles. Decreased visual acuity as well as lack of experience was significantly correlated with difficulties in the correct instillation of eye drops.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Dietlein et al, participants had used eye drop bottles earlier, but only a fraction had previous experience with single-use eye-drop containers (27%-39%). 15 The problems with selfinstillation from the single-dose containers were associated with lack of experience with using them. The authors concluded that there was a training effect involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation